2009
DOI: 10.1017/s0007114509990857
|View full text |Cite
|
Sign up to set email alerts
|

Equol in milk of dairy cows is derived from forage legumes such as red clover

Abstract: The intake of isoflavones and the resulting equol contents of both plasma and milk of the same red clover-fed cows are reported for the first time in cyclic change-over design study. Cows were fed four different red clover silages and two timothy -meadow fescue silages as controls. The red clover silages contained daidzein, formononetin, biochanin A and genistein, whereas the timothy -meadow fescue silages contained no isoflavones. We found a strong association (y ¼ 0·071x þ 2·75, R 2 0·71) between the formono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
74
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 31 publications
13
74
1
2
Order By: Relevance
“…Thus, apparent recovery from feed to milk of daidzein was 2.5 µg/mg, of genistein was 5.0 µg/mg and of glycitein was 3.9 µg/mg in group S while apparent recoveries of individual isoflavones in C were enormously high. Similar findings were also reported by e. g. Mustonen et al (2009), Andersen et al (2009) or Steinshamn et al (2008) who studied the recovery of red clover-derived phytoestrogens suggesting that the transfer rate of isoflavonoids from feed to milk is higher at low intake than at higher intake. Table 3.…”
Section: Intake Ofsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, apparent recovery from feed to milk of daidzein was 2.5 µg/mg, of genistein was 5.0 µg/mg and of glycitein was 3.9 µg/mg in group S while apparent recoveries of individual isoflavones in C were enormously high. Similar findings were also reported by e. g. Mustonen et al (2009), Andersen et al (2009) or Steinshamn et al (2008) who studied the recovery of red clover-derived phytoestrogens suggesting that the transfer rate of isoflavonoids from feed to milk is higher at low intake than at higher intake. Table 3.…”
Section: Intake Ofsupporting
confidence: 88%
“…This further supports the beneficial potential of orally administered equol to individuals classified as equol "non-producers". From the range of foods commonly consumed by humans, cow's milk is presumably the only nutritive that can contain appreciable amounts of equol itself (Mustonen et al, 2009, Steinshamn et al, 2008 thus bovine milk can be considered as a potential source of equol for non-equol producers. Furthermore, in a recent study, Kuhnle et al (2008) reported low content of equol in various commercially available dairy products except butter.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is well established in human populations $20-30% of individuals can produce equol at relatively low concentrations compared to animals (Frankenfeld, 2011;Lephart, 2013a;Setchell & Clerici, 2011) and recent evidence indicates that equol is present in plant products such as beans, cabbage, and lettuce (Hounsome et al, 2009(Hounsome et al, , 2010. Further research has revealed that equol concentrations in low-soy consuming US populations reflect equol intakes from mammalian (cow) milk sources (Frankenfeld, 2011;Hoikkala et al, 2007;Mustonen et al, 2009) that can be as high as 1.5 mg/kg in cow's milk (Höjer et al, 2012). Notably, the metabolism of Rand S-equol in humans appears to be similar (Setchell et al, 2005(Setchell et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, changes during ensiling were not studied. Silages prepared from primary growth of a mixture of timothy-meadow fescue (Festuca pratense) contained no isoflavones (Mustonen et al, 2009). Also data of Höjer et al (2012) prove that red clover is the main source of isoflavones in silages of legume-grass mixtures (Table 4).…”
Section: Isoflavones In Foragesmentioning
confidence: 96%
“…Metabolic changes of equol precursors caused the delay of equol occurrence. Mustonen et al (2009) determined the isoflavones in pooled samples of blood taken before morning feeding with silages and 3 h thereafter. The contents of formononetin were 0.004-0.035 mg/l and traces in plasma of dairy cows fed with red clover silages and grass silages, respectively.…”
Section: Isoflavones and Equol In Bovine Plasma And Milkmentioning
confidence: 99%